Evaluasi Kinerja Operasional pada Bus Trans Jatim Koridor V Rute Surabaya - Bangkalan - Yasmine Anisatul Lutfiah; Fithri Estikhamah; Nugroho Utomo (Universitas Batanghari Jambi, 2026)
Trans Jatim is a provincial bus-based public transport system initiated by the East Java Government to strengthen regional connectivity and alleviate traffic congestion, particularly within the Gerbangkertosusila metropolitan area. One of the newly introduced corridors, Corridor V, operates along the Surabaya–Bangkalan route via the Suramadu Bridge. This study aims to assess the operational performance of this corridor by focusing on three key indicators: load factor, travel time, and headway. A field survey with an observational approach was conducted to collect primary data directly from actual operations. The findings indicate that the average load factor reached only 42%, which falls short of the required minimum standard of 70%. In contrast, the average travel time of 118 minutes and headway of 20 minutes both meet the acceptable thresholds outlined in official technical guidelines. These results reveal that among the evaluated indicators, only the load factor fails to comply with the service standards. The insights from this research are expected to serve as a reference for enhancing the efficiency and service quality of the Trans Jatim Bus Corridor V in a more sustainable manner.